On the question of reasons for beginning of Рerestroika (based on USSR and Siberian materials) - S. A. Velichko; V. A. Kutepov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study of the reasons for the beginning of perestroika in the USSR (1985–1991). The purpose of the article is to show that democratic transformations began not as a result of the backwardness of isolation in the USSR, but in connection with urbanization, the growth of the level of education and international communications. Also, the beginning of perestroika is associated with the crisis phenomena of the Soviet system, which are considered in the article both on the basis of all-Russian and Siberian materials.